GAYATRI DALAM SEJARAH SINGHASARI DAN MAJAPAHIT - Deny Yudo Wahyudi (Jurnal Sejarah dan Budaya, 2013)
Abstrak: Gayatri is an important woman figure in history of Majapahit. As a main family member, she had central role, although her role is invisible. Her status as Rajapatni gave her a big power, so she ascended her husband’s throne after her son in law, who has no son, died. Her Pendharmaan becomes an important source to be studied because of its vague of supporting data.